The influence of temperature on rheological properties of blood mixtures with different volume expanders-implications in numerical arterial hemodynamics simulations - Georgiou, Georgios C.; Papaharilaou, Yannis; Anayiotos, Andreas; Valant, Andreja Zupančič; Ziberna, Lovro (My University, 2011)
During the complicated cardiac surgery on a non-beating heart with cardiopulmonary bypass, protection of the heart is accomplished by injecting cold cardioplegic solutions. In most forms of circulatory shock, it is necessary to immediately restore the circulating volume. Intravenous solutions of volume expanders, such as hydroxyethyl starch and dextrans, are used to increase the volume of fluid in the circulating blood. In this work, blood samples of six donors were obtained and used to prepare mixtures with different volume expanders in concentrations ranging from 10 to 50 vol./vol.%. The flow curves of all mixtures in the temperature range from 4°C to 37°C were constructed and fitted to the Herschel-Bulkley model, in order to extract the shear thinning and yield stress parameters. To assess the influence of the observed changes in the rheological properties of blood on the hemodynamics in arterial vasculature, a realistic three-dimensional rigid-wall computational model was constructed from MRI images of the right carotid bifurcation obtained in vivo from a healthy male volunteer. The time-varying flow field was numerically computed using the Newtonian model as well as the Herschel-Bulkley model with the Papanastasiou regularization. The numerical simulations indicate only moderate changes in the time-averaged flow field that become accentuated when the instantaneous flow field is considered. We also found that although the influence of temperature, hematocrit, and volume expanders on hemodynamics is significant, this can primarily be attributed to the changes in the nominal viscosity of the flow medium.
Keywords: Blood; Hemodynamics; Hemorheology; Herschel-Bulkley model; Volume expanders